Development of Multicultural-Based Arabic Learning Curriculum: Challenges and Opportunities in the Global Era/ تطوير منهج تعلّم اللغة العربية على أساس متعدد الثقافات: التحديات والفرصات في عصر العولمة - Nurul Ainiy; Isnainiyah Isnainiyah (Universitas Negeri Malang, 2022)
Multiculturalism is the social reality of Indonesian society, and it cannot be separated from other aspects of life, especially education. In learning Arabic, multiculturalism not only comes from the diversity of students' backgrounds, but also considers learning orientation, learning style, learning objectives and past educational history. This multicultural phenomenon is a challenge in learning Arabic in the era of globalization, but if these challenges are properly managed, they can be turned into valuable opportunities for the advancement of Arabic learning in the future. Therefore, efforts are needed to design an appropriate curriculum with multicultural principles in learning Arabic. This research aims to delve into the principles of curriculum development on a multicultural basis for teaching Arabic, opportunities, and challenges in the application. This paper uses the Library Research method, which is written based on the results of a study of various relevant library materials. The data collected is qualitative data. The data was analyzed by data reduction, data classification, data description and conclusion.إن تعدد الثقافات هو الواقع الاجتماعي للمجتمع الإندونيسي، ولا يمكن فصله عن جوانب الحياة الأخرى، وخاصة التعليم. في تعلم اللغة العربية، لا يأتي تعدد الثقافات فقط من تنوع خلفيات الطلاب، ولكن ينظر أيضًا في توجه التعلم وأسلوب التعلم وأهداف التعلم والتاريخ التعليمي السابق. تعدّ هذه الظاهرة أي متعدد الثقافات تحديًا في تعلم اللغة العربية في العصر العولمة، ولكن إذا تم توجيه هذه التحديات بشكل صحيح، يمكن تحويلها إلى فرص ثمينة لتقدم تعلم اللغة العربية في المستقبل. لذلك هناك حاجة إلى بذل جهود لتصميم المنهج الدراسي المناسب بمبادئ متعدد الثقافات في تعلم اللغة العربية. ويهدف هذا البحث إلى التعمق في مبادئ تطوير المنهج الدراسي على أساس متعدد الثقافات لتعليم اللغة العربية، وتحديات وفرصات في تطبيقها. يستخدم هذ البحث طريقة البحث المكتبي (library research)، التي تتم كتابتها بناءً على نتائج دراسة مواد مكتبية متنوعة ذات صلة. نوع البيانات هي البيانات النوعية. وتم تحليل البيانات بإجراءات تقليل البيانات، وتصنيف البيانات، ووصف البيانات، والاستنتاج